Mycoplasma hyopneumoniae Infection Activates the NOD1 Signaling Pathway to Modulate Inflammation - Liu, Wei; Jiang, Pengcheng; Yang, Keli; Song, Qiqi; Yuan, Fangyan; Liu, Zewen; Gao, Ting; Zhou, Danna; Guo, Rui; Li, Chang; Sun, Pei; Tian, Yongxiang (Frontiers in Cellular and Infection Microbiology, 2022)
Mycoplasma hyopneumoniae is highly contagious pathogen that cause porcine enzootic pneumonia, which elicits prolonged inflammatory responses modulated by pattern recognition receptors (PRRs). Although, significant advances have been made on Toll-Like receptors in the recognition of M. hyopneumoniae, the role of nucleotide-binding oligomerization domain 1 (NOD1) in M. hyopneumoniae infected cells remains poorly elucidated. This present study revealed that M. hyopneumoniae activate NOD1-RIP2 pathway and co-localize with host NOD1 during infection. Knockdown of NOD1 by siRNA significantly impair the TRIF and MYD88 pathway, as well as the activation of TNF-α. In contrast, the overexpression of NOD1 significantly suppressed M. hyopneumoniae proliferation. Furthermore, we described, for the first time, the interactions between M. hyopneumoniae mhp390 and NOD1 receptor, which suggested the involvement of mhp390 and NOD1 in the recognition of M. hyopneumoniae. Collectively, these findings may enrich our understanding of the interactions between PRRs and M. hyopneumoniae, as well as the functions of NOD1 in the host defense against M. hyopneumoniae infection.